Organic Reactions 1988
DOI: 10.1002/0471264180.or035.02
|View full text |Cite
|
Sign up to set email alerts
|

The Persulfate Oxidation of Phenols and Arylamines (TheElbs and theBoyland–Sims Oxidations)

Abstract: A phenolate anion reacts with persulfate ion in alkaline solution to yield a product in which a sulfate group enters the ring para or ortho to the phenolic group. Para substitution predominates. Subsequent acid‐catalyzed hydrolysis yields the dihydric phenol. The reaction was discovered by Karl Elbs in 1893 and named the Elbs persulfate oxidation . The reaction is generally applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 173 publications
3
40
0
Order By: Relevance
“…In the Boyland-Sims oxidation, the amine-Osulfonate was the obvious choice that was supported by a number of kinetic studies. [1] This was questioned by Edward and Whiting [2] who claimed that the molecule formed by sulfonating N,N-dimethylaniline-N-oxide (1) did not rearrange to the o-sulfate(2) but rather decomposed by hydrolysis. However, repetition of this work under strictly anhydrous conditions showed that the sulfonated N-oxide(1) indeed rearranged to the o-sulfate (2) in good yield (Scheme 2).…”
Section: Mechanisms Of the Reactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the Boyland-Sims oxidation, the amine-Osulfonate was the obvious choice that was supported by a number of kinetic studies. [1] This was questioned by Edward and Whiting [2] who claimed that the molecule formed by sulfonating N,N-dimethylaniline-N-oxide (1) did not rearrange to the o-sulfate(2) but rather decomposed by hydrolysis. However, repetition of this work under strictly anhydrous conditions showed that the sulfonated N-oxide(1) indeed rearranged to the o-sulfate (2) in good yield (Scheme 2).…”
Section: Mechanisms Of the Reactionsmentioning
confidence: 99%
“…[23] While there are a few exceptions (some irrelevant to this discussion), the p-substituted phenols generally have lower bond dissociation energies in the range of 1-5 kcal/ mol than either the o-or m-substituted isomers in accord with this proposal. Bader and Jahngen [24] have reported a 9% increase in yield in the synthesis of gentisaldehyde in the presence of allylbenzene, a sulfate radical trap, although in other cases (such as o-nitrophenol [1]) radical traps have little effect. It seems clear that the relative rates of the radical and non-radical pathways vary widely with the nature of the phenol.…”
Section: Low Yields and Recovery Of Starting Materialsmentioning
confidence: 99%
See 3 more Smart Citations